Fractal Analysis of Pore–Throat Structures in Triassic Yanchang Formation Tight Sandstones, Ordos Basin, China: Implications for Reservoir Permeability and Fluid Mobility - Pan Li (Fractal and Fractional)
Microscopic pore–throat structures, known for their complexity and heterogeneity, significantly influence the characteristics of tight sandstone reservoirs. Despite the advances in geological research, studies leveraging fractal theory to elucidate differences across pore scales are limited, and conventional testing methods often fail to effectively characterize these complex structures. This gap poses substantial challenges for the exploration and evaluation of tight oil reservoirs, highlighting the need for refined analytical approaches. This study addresses these challenges by applying fractal analysis to the pore–throat structures of the Triassic Yanchang Formation tight sandstones in the Wuqi Area of the Ordos Basin. Employing a combination of experimental techniques—including pore-casted thin sections, scanning electron microscopy, high-pressure mercury intrusion, constant-rate mercury intrusion, and nuclear magnetic resonance (NMR)—this study analyzes the fractal dimensions of pore–throats. Findings reveal that tight sandstone reservoirs are predominantly composed of micron-scale pore–throats, displaying complex configurations and pronounced heterogeneity. Fractal curves feature distinct inflection points, effectively categorizing the pore–throats into large and small scales based on their mercury intrusion pressures. By linearly fitting slopes of fractal curves, we calculate variable fractal dimensions across these scales. Notably, NMR-derived fractal dimensions exhibit a two-segment distribution; smaller-scale pore–throats show less heterogeneity and spatial deformation, resulting in lower fractal dimensions, while larger-scale pore–throats, associated with extensive storage capacity and significant deformation, display higher fractal dimensions.